Material Advancements in Fabrication of Mixed‐Matrix Membranes. Issue 5 (24th April 2013) - Nasir, R.; Mukhtar, H.; Man, Z.; Mohshim, D. F.
Abstract The mixed‐matrix membrane (MMM) is a new membrane material for gas separation and plays a vital role for the advancement of current membrane‐based separation technology. Blending between inorganic fillers like carbon molecular sieves, zeolite, metal oxides, silica and silica nanoparticles, carbon nanotubes, zeolitic imidazolate framework, metal organic framework, and glassy and rubbery polymers etc. is possible. Due to mechanical, thermal, and chemical stability, these membranes achieve high permeability and selectivity as compared to pure polymeric materials. Despite of these advantages, the MMM performances are still below industrial expectations because of membrane defects and related processing problems as well as the nonuniform dispersion of fillers in MMMs. Material selection for organic and inorganic phases, preparation techniques, material advancements, and performance of MMMs are discussed. Issues and challenges faced during MMM synthesis as well as problem solutions are highlighted.